Buzz off! An evaluation of ultrasonic acoustic vibration for the disruption of marine micro‐organisms on sensor‐housing materials. (8th November 2016) - McQuillan, J.S.; Hopper, D.J.; Magiopoulos, I.; Arundell, M.; Brown, R.; Shorter, S.; Mowlem, M.C.; Pascal, R.W.; Connelly, D.
Abstract: Biofouling is a process of ecological succession which begins with the attachment and colonization of micro‐organisms to a submerged surface. For marine sensors and their housings, biofouling can be one of the principle limitations to long‐term deployment and reliability. Conventional antibiofouling strategies using biocides can be hazardous to the environment, and therefore alternative chemical‐free methods are preferred. In this study, custom‐made testing assemblies were used to evaluate ultrasonic vibration as an antibiofouling process for marine sensor‐housing materials over a 28‐day time course. Microbial biofouling was measured based on (i) surface coverage, using fluorescence microscopy and (ii) bacterial 16S rDNA gene copies, using Quantitative polymerase chain reaction (PCR). Ultrasonic vibrations (20 KHz, 200 ms pulses at 2‐s intervals; total power 16·08 W) significantly reduced the surface coverage on two plastics, poly(methyl methacrylate) and polyvinyl chloride (PVC) for up to 28 days. Bacterial gene copy number was similarly reduced, but the results were only statistically significant for PVC, which displayed the greatest overall resistance to biofouling, regardless of whether ultrasonic vibration was applied. Copper sheet, which has intrinsic biocidal properties was resistant to biofouling during the early stages of the experiment, but inhibited measurements made by PCR and generated inconsistent results later on. Significance and Impact of the Study: In this study, ultrasonic acoustic vibration is presented as a chemical‐free, ecologically friendly alternative to conventional methods for the perturbation of microbial attachment to submerged surfaces. The results indicate the potential of an ultrasonic antibiofouling method for the disruption of microbial biofilms on marine sensor housings, which is typically a principle limiting factor in their long‐term operation in the oceans. With increasing deployment of scientific apparatus in aquatic environments, including further offshore and for longer duration, the identification and evaluation of novel antifouling strategies that do not employ hazardous chemicals are widely sought. Abstract : Significance and Impact of the Study: In this study, ultrasonic acoustic vibration is presented as a chemical‐free, ecologically friendly alternative to conventional methods for the perturbation of microbial attachment to submerged surfaces. The results indicate the potential of an ultrasonic antibiofouling method for the disruption of microbial biofilms on marine sensor housings, which is typically a principle limiting factor in their long‐term operation in the oceans. With increasing deployment of scientific apparatus in aquatic environments, including further offshore and for longer duration, the identification and evaluation of novel antifouling strategies that do not employ hazardous chemicals are widely sought.